Perturbation of upper gastrointestinal transit and antroduodenal motility by experimentally applied stress: the role of beta-adrenoreceptor mediated pathways. Issue 11 (November 1989) - O'Brien, J D; Thompson, D G; Day, S J; Burnham, W R; Walker, E
Abstract : A series of three experiments were performed on healthy adult volunteers to investigate the possible role played by beta-adrenoreceptor mediated pathways in the disturbance of human upper intestinal motor function by hand immersion in cold water. In the first experiment, (an extended pilot study on one individual), orocaecal transit of a standard meal was measured on 36 occasions with and without cold water stimulation and with and without a series of alpha and beta blocking drugs. Cold water stimulation consistently delayed transit in this individual, an effect which was attenuated by prior beta-blockade. In a double blind trial of the effect of beta-blocker atenolol v placebo on transit in nine individuals, a consistent reduction in the cold water induced transit delay was observed (p less than 0.01) independent of any direct effect of beta-blockade. In the third experiment seven individuals underwent repeated studies of antroduodenal pressure activity comparing the effects of cold and warm water stimulation with and without beta blockade to determine whether the observed transit effect could be related to an action on gastrointestinal motility. Cold water stimulation reduced antroduodenal motility, but no consistent effects of previous beta blockade were noted. These studies indicate the presence of a beta-adrenoreceptor mediated pathway in the cold water induced delay of orocaecal transit but not in the inhibition of gastroduodenal motility. Further studies are indicated to determine the site and mode of action of this transit effect more precisely.